Cost & effect : using integrated cost systems to drive profitability and performance - Kaplan, Robert S.; Cooper, Robin (Boston : Harvard Business School Press, 1998)
The authors demonstrate how the principles of activity-based costing and other advanced cost management techniques, such as target and kaizen costing, can drive business performance. The book in a nutshell provides a comprehensive overview of the principles, possible uses and benefits of activity-based management that will help managers.
Includes bibliographical references (p. [323]-345) and index.
rua 19/07/13
Loans
Keywords: Activity-based costing; Cost and effect; Activity based management; Performance management system